Proceedings of the Fourteenth Annual ACM-SIAM Symposium on Discrete Algorithms 2020
DOI: 10.1137/1.9781611975994.166
|View full text |Cite
|
Sign up to set email alerts
|

Complexity and Parametric Computation of Equilibria in Atomic Splittable Congestion Games via Weighted Block Laplacians

Abstract: We settle the complexity of computing an equilibrium in atomic splittable congestion games with player-specific affine cost functions l e,i (x) = a e,i x + b e,i as we show that the computation is PPAD-complete. To prove that the problem is contained in PPAD, we develop a homotopy method that traces an equilibrium for varying flow demands of the players. A key technique for this method is to describe the evolution of the equilibrium locally by a novel block Laplacian matrix where each entry of the Laplacian is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 52 publications
2
11
0
Order By: Relevance
“…In other cases, all known formulations lead to nonstandard LCPs, which cannot be handled by the "vanilla" version of Lemke's algorithm, and require variants of the algorithm to be devised, e.g., see [Garg et al, 2018;Meunier and Pradeau, 2019]. Finally in some cases, it is not known if the derived LCPs can be solved via any variant of Lemke's algorithm, thus leading to the development of entirely new pivoting algorithms [Klimm and Warode, 2020]. These characteristics of the LCP approach make it somewhat insufficient as a general purpose PPAD-membership technique.…”
Section: Main Previous Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…In other cases, all known formulations lead to nonstandard LCPs, which cannot be handled by the "vanilla" version of Lemke's algorithm, and require variants of the algorithm to be devised, e.g., see [Garg et al, 2018;Meunier and Pradeau, 2019]. Finally in some cases, it is not known if the derived LCPs can be solved via any variant of Lemke's algorithm, thus leading to the development of entirely new pivoting algorithms [Klimm and Warode, 2020]. These characteristics of the LCP approach make it somewhat insufficient as a general purpose PPAD-membership technique.…”
Section: Main Previous Approachesmentioning
confidence: 99%
“…Indeed, coming up with proofs of existence that also guarantee rationality of solutions has been a topic of interest in the area since the very early days, way before the introduction of the relevant computational complexity classes, e.g., see [Eaves, 1976;Lemke and Howson, 1964;Lemke, 1965;Howson, 1972]. Driven by those classic results, a significant literature in computer science has attempted, and quite often has succeeded in placing the corresponding computational problems in PPAD, for several of the application domains mentioned above, including games [Sørensen, 2012;Hansen and Lund, 2018;Kintali et al, 2013;Klimm and Warode, 2020;Meunier and Pradeau, 2019], markets [Vazirani and Yannakakis, 2011;Garg and Vazirani, 2014;Garg, 2017;Garg et al, 2018], as well as the more recent domain of auto-bidding auctions [Chen et al, 2021a].…”
Section: Introductionmentioning
confidence: 99%
“…b) Consumers' constraints and parameters: We consider a set of N = 2000 consumers who have demand constraints of the form: (11) where En is the total energy needed by n, and x n,t , x n,t (physical) bounds on the power allowed at time t. The utility functions have the form un(xn) def = −ωn xn − yn 2 , with yn a preferred charging profile. Simulation parameters are chosen as follows:…”
Section: Application To Demand Response and Electricity Flexibilimentioning
confidence: 99%
“…The notion of Nash Equilibrium (NE) [9] has emerged as the central solution concept in game theory. However, the computation of an NE is considered a challenging problem: indeed, recent works have proved the theoretical complexity of the problem (PPAD-completeness [10], [11]). In continuous games, NEs can be characterized as solutions of Variational Inequalities (VI) [12], a characterization we adopt throughout this work.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding player-specific affine costs, Harks and Timmermans [21] described a polynomial algorithm for parallel-edge networks, and Bhaskar and Lolakapuri [5] presented an exponential algorithm for general convex functions. Very recently, Klimm and Warode showed that the computation with player-specific affine costs is PPAD-complete for general networks [25].…”
Section: Introductionmentioning
confidence: 99%